The first tests of a large-area light detector equipped with metallic magnetic calorimeters for scintillating bolometers for the LUMINEU neutrinoless double beta decay search - Gray, David; Enss, Christian; Fleischmann, Andreas; Gastaldo, Loredana; Velte, Clemens; Hengstler, Daniel; Kempf, Sebastian; Loidl, M.; Navick, X. F.; Rodrigues, M. (Journal of low temperature physics, 2016)
Future rare-event searches using scintillating crystals need very low background levels for high sensitivity; however, unresolved pile-up can limit this. We present the design and fabrication of large-area photon detectors based on metallic magnetic calorimeters (MMCs), optimized for fast rise times to resolve close pile-up. The first prototypes have been characterized using Fe-55 X-rays and ZnMoO$$_{4}$$4crystal scintillation light. A fast intrinsic rise time of 25-30 $$\upmu $$μs has been measured and has been compared to the 250 $$\upmu $$μs scintillation light pulse rise time constant. The difference indicates that the scintillation process limits the light pulse rise time. The fast rise time allows for a reduction of background due to close pile-up events as well as the study of the inherent crystal scintillation process. MMC-based photon detectors are shown to be a promising tool for scintillating crystal based rare event searches.
Gesehen am 31.07.2020